Designing Instagram Visual Content Templates to Strengthen Brand Identity - Jonathan Pehulisa Marbun (Kreator, 2026)
The development of information and communication technology has driven a significant transformation in marketing strategies, with social media, particularly Instagram emerging as one of the main platforms for building brand identity. This study aims to examine the design of Instagram visual content templates that play a role in strengthening brand image and character in the digital space. Using a qualitative descriptive approach and a literature review method, this research seeks to provide a comprehensive understanding of visual content design strategies. The findings indicate that effective visual content design requires consistency in the use of design elements such as color, typography, layout, and communication tone. Furthermore, six key steps are essential in content development, starting from theme selection, content conversion strategies, to performance evaluation. In conclusion, the application of consistent and strategic visual content template design can strengthen brand identity, enhance consumer trust, and expand marketing reach in the digital era.